find out the resultant displacement of the particle at x at time t.of y1(x,t)= 0.2 sin π (t-2x) and 1(x,y)= 0.2 sin π (t+ 2x)
Answers
Answered by
0
Answer:
0.4 sin(t) cos(2x)
Explanation:
1st equation : y1(x,t)= 0.2 sin π (t-2x)
2st equation : Y2(x,t)= 0.2 sin π (t+ 2x) ( assume this one corrected)
Y = Y1 + Y2
= 0.2 sin π (t-2x) + 0.2 sin π (t+ 2x)
= 0.2 ( 2 sin(t)cos(2x) ) ( sin(a-b) + sin(a+b) = 2sin(a).cos(b) )
= 0.4 sin(t) cos(2x)
so given the resultant displacement of the particle at x at time t.of y1 and Y2
Similar questions